How to Identify Context on Song Lyrics? A Case on Discourse Analysis on Eminem’s Song Entitled “When I’m Gone” - Betty Jeniari Tambunan; Joint Tondang; Yuliska Gurning; Citra Sani Sinaga; Sumiati Butar-Butar; Herman Herman (Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to analyzing a song lyric entitiled